Selective Reduction of Brain Docosahexaenoic Acid after Experimental Brain Injury and Mitigation of Neuroinflammatory Outcomes with Dietary DHA - Butt, Christopher M.; Harrison, Jordan L.; Rowe, Rachel K.; Jones, Jacob; Wynalda, Kelly M.; Salem, Norman, Jr.; Lifshitz, Jonathan; Pauly, James R. (Current Research: Concussion, 2017)
Background Docosahexaenoic acid (DHA) is an omega-3 fatty acid that is important for brain development and function, but the interactions of dietary DHA with fatty acid profiles, sensory sensitivities, and inflammation that may change after traumatic brain injury (TBI) are poorly understood. It is also unknown whether DHA alters experimental TBI outcomes measured more than 2 weeks after injury. The current study investigated whether dietary DHA, provided before (PreDHA) or after (PostDHA) experimental TBI, would improve outcomes for up to 24 days after injury.Methods Rats consumed predetermined diets for 28 days prior to midline fluid percussion injury (mFPI) or to sham surgery. The effects of PreDHA, TBI, and PostDHA on comprehensive fatty acid profiles, neuroinflammation, sensory sensitivity, and spatial learning were then evaluated.Results The results provided novel evidence that TBI selectively reduced brain DHA content, as injury did not decrease any other fatty acid that was measured. Furthermore, PreDHA and PostDHA attenuated injury-induced increases in sensory sensitivity as well as in tumor necrosis factor-α (TNF-α), interleukin-10, and interleukin-1β in the somatosensory cortex. However, [3H]PK11195 autoradiography showed that PostDHA was more effective than PreDHA in reducing microglial/macrophage activation in the somatosensory cortex, hippocampus, and substantia nigra. Spatial learning outcomes were largely unaffected by diet or injury, but PostDHA was associated with shorter swimming distances in the Morris water maze (MWM) at 15 days post-injury.Conclusion Overall, sufficient DHA intake may be necessary to replace DHA that is lost to TBI and may improve some symptoms of post-concussive syndrome (PCS) over an extended period through inflammation-related mechanisms.
Keywords: traumatic brain injury; docosahexaenoic acid; neuroinflammation; post-concussive syndrome